Propuesta de elaboración del capítulo referente a la granulometría de agregados para el concreto (2013)
This project of degree exposes a proposal for the Elaboration of the Chapter referring to the Granulometry of Aggregates for the Concrete. This chapter arises from the need to present a document that evidences the importance of knowing everything related to the aggregates used to make the concrete. The importance of the aggregates within the concrete mass is that, although it is composed of other elements such as cement paste, free water, trapped air, additions, fibers and additives that improve its characteristics, most of the properties of this , they are due to an adequate proportion and appropriate characteristics of the aggregates that allow to obtain as a result economic concrete and of excellent quality, that they fulfill depending on the use and the exhibition environment with some characteristics such as: easiness of placement, resistance at an early age, suitable mechanical properties, low permeability, tenacity, volume stability, long life in severe environments, among others. This project will focus on presenting the aggregates used for the concrete, its classification, its origin, its properties and the procedures used to ensure that the dosage of them is adequate to achieve resistant, manageable and economical concrete.